THE SIMILAR CHANGES OF GLUCOSE LEVELS BEFORE AND AFTER MODERATE INTENSITY EXERCISE ACUTELY IN THE MORNING AND EVENING - Ronik Harsono Kamal; Kristanti Wanito Wigati; Achmad Lefi (Universitas Airlangga, Surabaya, Indonesia, 2020)
Background: There is a lot of research on the importance of exercise but studies on the effective time of exercise regarding regulation of blood glucose levels are not clearly known. Objective: This study aimed to determine the comparison of changes in blood glucose levels before and after moderate intensity physical exercise in the morning and evening. Materials and Methods: Healthy men (n=34), age between 17-22 years, Body Mass Index (BMI) between 18.5-22.9 kg/m2 (normal Asia Pacific), participating in the morning (8.00 am) or evening group (20.00 pm) are asked to do moderate intensity physical exercise (55-70% of maximum heart rate) using ergocycle for a total of 40 minutes. Blood glucose levels 2 hours post prandial capillaries were taken before exercise and blood glucose levels after exercise were taken acutely. Results: The mean decrease in blood glucose levels in the morning group was ± 8.353 ± 9.16 mg/dL and in the evening group was ± 6.294 ± 10.10 mg/dL. Blood glucose levels decreased significantly for the morning group (p=0.002) and the evening group (p=0.021). The comparison of changes in blood glucose levels between the morning and evening groups was not significant (p=0.538). Conclusion: There was no difference between morning or evening exercise related to changes in blood glucose levels.